Leishmania in dog (Canis lupus familiaris) in the Metropolitan area of Caracas- Venezuela. (Gaceta de Ciencias Veterinarias, 2021)
Clinical case of leishmaniasis is described for female dog (Canis lupus familiaris) in the metropolitan area of Caracas, Venezuela. No previous reports can be found for the disease in animals inside the metropolitan area of Caracas.
Keywords: Leishmania; dog; Caracas; Venezuela